The darkness in the theatre : Merleau-Ponty and film - MacGillivray, Jenina, 1973- (2001)
Thesis (M.Phil.)--Memorial University of Newfoundland, 2004. Philosophy Bibliography: leaves 88-89 This thesis will examine the notion of the "virtual body" present in the work of Maurice Merleau-Ponty, with particular attention paid to the Phenomenology of Perception. For Merleau-Ponty, the body is not, as it is in empiricism and idealism, a simple transmitter of data for the mind. For Merleau-Ponty, the body must be seen as situated, that is, as a lived body. The complex lived structures of the body, i.e., its operative intentionality, memory, spatial and temporal orientation, all contribute to the way in which the body is the "ground" of reflexive understanding. That is, for Merleau-Ponty, the pre-reflexive- or, the lived body - grounds the reflexive. The body figures in consciousness, and in understanding, in a developmental way. Rather than seeing consciousness and understanding as a formal "object positing' system, Merleau-Ponty maintains that it is relational and cannot be understood apart from its phenomenal field. Perception is the best expression of this relational structure, for when we perceive and understand objects, we carry forward all our bodily experience - Merleau-Ponty calls it the "body image"-and this allows for the concurrent working out and clarification of meaning. This bodyimage, or virtual body, can be examined well through the film experience. So, as Merleau-Ponty suggests, we will look to film, for, as Merleau-Ponty puts it in "The Film and the New Psychology": "[t]he movies are well suited to make manifest the union of mind and body, mind and world, and the expression of one in the other."